2012
DOI: 10.4103/0972-5229.99107
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin in prophylaxis of deep vein thrombosis in Asian general surgical patients: A Kashmir experience

Abstract: Background and Objectives:Deep vein thrombosis (DVT) occurs at a lower rate in Asia than in the rest of the world. We wanted to study the significance and efficacy of low molecular weight heparin (LMWH) in prophylaxis of DVT in major general surgical patients in the Kashmir Valley (India, Asia) so as to make it a routine in our patients.Patients and Methods:This was a prospective study in which the effect of LMWH was compared with no prophylaxis.Results:LMWHs are more effective than no prophylaxis in the preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…One study [17] included patients who underwent abdominal surgery, four studies [7, 8, 12, 14] included only gastric cancer patients, while seven studies [10, 11, 13, 15, 16, 19, 20] examined patients with colorectal cancer. The other two studies [9, 18] looked at patients after general surgery procedures, the majority of which were abdominal operations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study [17] included patients who underwent abdominal surgery, four studies [7, 8, 12, 14] included only gastric cancer patients, while seven studies [10, 11, 13, 15, 16, 19, 20] examined patients with colorectal cancer. The other two studies [9, 18] looked at patients after general surgery procedures, the majority of which were abdominal operations.…”
Section: Resultsmentioning
confidence: 99%
“…The actual number of patients diagnosed with symptomatic DVT was 14 of 560 (2.5 %). Note that Dar et al [9] routinely performed venous duplex scans to detect DVT, which probably explains the higher rate of DVT compared to that of the other studies. In comparison, Ho et al [20] used routine clinical assessment supplemented by a hand‐held Doppler probe to detect venous flow on muscle squeezing as an indication for venous duplex scanning.…”
Section: Resultsmentioning
confidence: 99%
“…In abdominal surgery, a prophylactic dose of low-molecular-weight heparin is administered to patients at risk of venous thromboembolic disease, so the initiation of this in the preoperative period may be beneficial in reducing the formation of PAA without the risk of bleeding. as seen in these patients [ 9 ].…”
Section: Introductionmentioning
confidence: 61%
“…Studies on Asian patients have shown increased rates of complications in the LMWH group compared to non LMWH group. These ranged from small hematomas and minor ooze to major intra-abdominal and intraluminal bleeding [17,18]. Interestingly though, studies which used LMWH in Asian patients invariably demonstrated a zero rate of symptomatic VTE [13].…”
Section: Discussionmentioning
confidence: 99%